PERENCANAAN KURIKULUM DALAM PENGEMBANGAN BAHASA ARAB ULUMUDDIN UTEUNKOT-CUNDA KOTA LHOKSEUMAWE - Fuadi, Samsul (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to determine planning implementing Ulumuddin Arabic language curriculum management in Lhokseumawe City. This study uses qualitative methods, so the data sources are informants, namely the leadership of Dayah Ulumuddin, Deputy Head of Education Dayah Ulumuddin, Head of Dayah, Deputy Head of Dayah, Language Builder, teachers, and santri. In addition, documents are also used, including documents of Head of Dayah Salafy, Deputy Head of Dayah Salafy, especially in the curriculum, and administration documents. The researcher obtained data through observation including the process of developing Arabic language activities, the process of extra-curricular activities, decision making, teacher council meetings, facilities and infrastructure, socialization, and program management, as well as institutional management processes and others. The results of the research are planning is done by first considering the aspects related to the curriculum, both the planning process by involving many people, the contents of the curriculum, the curriculum system to be applied, the availability of resources both human and non-human resources. Then what the Dayah wants to achieve related to fostering Arabic, then formulates the steps in achieving it through a planning program.